2006
DOI: 10.1128/aem.72.5.3600-3607.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Conventional and Organic Production Practices on the Prevalence and Antimicrobial Resistance of Campylobacter spp. in Poultry

Abstract: Intestinal tracts of broilers and turkeys from 10 conventional broiler farms and 10 conventional turkey farms, where antimicrobials were routinely used, and from 5 organic broiler farms and 5 organic turkey farms, where antimicrobials had never been used, were collected and cultured for Campylobacter species. A total of 694 Campylobacter isolates from the conventional and organic poultry operations were tested for antimicrobial resistance to nine antimicrobial agents by the agar dilution method. Although Campy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
152
7
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(180 citation statements)
references
References 41 publications
(47 reference statements)
20
152
7
1
Order By: Relevance
“…Two studies found a significantly higher prevalence in organic compared to conventional broilers on farm and processing level, whereas one study (Luangtongkum et al, 2006) did not find a significant difference (p>0.05). Heuer et al (2001) found a significantly higher (p<0.001) flock prevalence in organic compared to conventional broilers, although they did not detect a difference in broiler prevalence.…”
Section: Broilersmentioning
confidence: 85%
“…Two studies found a significantly higher prevalence in organic compared to conventional broilers on farm and processing level, whereas one study (Luangtongkum et al, 2006) did not find a significant difference (p>0.05). Heuer et al (2001) found a significantly higher (p<0.001) flock prevalence in organic compared to conventional broilers, although they did not detect a difference in broiler prevalence.…”
Section: Broilersmentioning
confidence: 85%
“…foram isolado de 100% das amostras investigadas. Outros autores também encontraram uma alta frequência de Campylobacter em frangos de criação orgânica, variando de 66% a 80% (Cui et al 2005, Luangtongkum et al 2006, Soonthornchaikul et al 2006. A elevada ocorrência de Campylobacter spp.…”
Section: Discussionunclassified
“…For example, resistance to tetracycline has been found in 26 different bacterial genera and in 60 species from swine manure (Stine et al, 2007). Furthermore, with the wider use of antibiotics, multiple drug resistance often develops (Chen et al, 2008;D'Lima et al, 2007;Luangtongkum et al, 2006). A study conducted in the 1980s on swine manure showed low levels of multiple drug resistance (Hanzawa et al, 1984).…”
Section: Use Of Antibiotics In Food Animal Industry and Development Omentioning
confidence: 99%